2021
DOI: 10.1080/21655979.2021.2009321
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic tensile strain facilitates proliferation and migration of human aortic smooth muscle cells and reduces their apoptosis via miRNA-187-3p

Abstract: The cardiovascular is a system that contains extremely complex mechanical factors, in which the circulatory flow of blood has rich mechanical laws. Many studies have revealed that mechanical factors play a very important role in the process of revascularization. Hence, it is essential to investigate the mechanical factors in the process of revascularization in depth. A cyclic tensile strain (CTS) was applied to human aortic smooth muscle cells (HASMCs) at a frequency of 1 Hz and amplitudes of 5%, 10% and 15%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 59 publications
0
0
0
Order By: Relevance
“…Abnormal expression of miR‐187‐3p has been observed in several tumors, including breast cancer, 15 peripheral T‐cell lymphoma, 16 osteosarcoma, 17 and hepatocellular carcinoma, 18 with implications for unfavorable clinical outcomes. Moreover, miR‐187‐3p has been implicated in the treatment of temporal lobe epilepsy, 19 type 2 diabetes, 20,21 alleviating damage caused by ischemia–reperfusion, 22,23 and promoting the growth of human aortic smooth muscle cells for the prevention and treatment of cardiovascular diseases 24 . In the context of bone homeostasis regulation, studies have indicated a decrease in miR‐187‐3p expression after treating bone cells with titanium 25 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abnormal expression of miR‐187‐3p has been observed in several tumors, including breast cancer, 15 peripheral T‐cell lymphoma, 16 osteosarcoma, 17 and hepatocellular carcinoma, 18 with implications for unfavorable clinical outcomes. Moreover, miR‐187‐3p has been implicated in the treatment of temporal lobe epilepsy, 19 type 2 diabetes, 20,21 alleviating damage caused by ischemia–reperfusion, 22,23 and promoting the growth of human aortic smooth muscle cells for the prevention and treatment of cardiovascular diseases 24 . In the context of bone homeostasis regulation, studies have indicated a decrease in miR‐187‐3p expression after treating bone cells with titanium 25 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, miR-187-3p has been implicated in the treatment of temporal lobe epilepsy, 19 type 2 diabetes, 20,21 alleviating damage caused by ischemia-reperfusion, 22,23 and promoting the growth of human aortic smooth muscle cells for the prevention and treatment of cardiovascular diseases. 24 In the context of bone homeostasis regulation, studies have indicated a decrease in miR-187-3p expression after treating bone cells with titanium. 25 Research has revealed that miR-187-3p inhibits the osteogenic differentiation of human osteoblast precursor cells (hFOB 1.19) by suppressing cannabinoid receptor 2.…”
Section: Introductionmentioning
confidence: 99%